French-Medium Instruction in Anglophone Canadian Higher Education: The Plurilingual Complexity of Students and Their Instructors - Marshall, Steve; Moore, Danièle; Himeta, Mariko (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2021)
In this article, we analyze the plurilingualism of instructors and their students in a program taught through the medium of French at a multilingual, Anglophone university in Western Canada. We employ the lenses of plurilingualism and plurilingual competence in the analysis of data from a one-year qualitative study of plurilingualism across the disciplines at the university. We analyze interview data and students’ writing samples, focusing on how French and other languages are used by instructors and students in classes, and on the professional dilemma that instructors face in such courses: are they disciplinary experts and/or French immersion teachers? In our discussion, we suggest that instructors’ and students’ classroom practices are the result of several factors, including institutional discourses around plurilingualism and the French language, personal beliefs and ideologies, experiences of mobility from France and Quebec to British Columbia (instructors), and normative practices previously experienced in French immersion schools (students).